2021
DOI: 10.3390/ani11030623
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Bone Quality, Egg Production and Eggshell Quality in Laying Hens at the End of an Extended Production Cycle (105 Weeks)

Abstract: (1) Background: Nowadays the industry aims to improve lay persistency for extended cycles (100 weeks or longer) to make egg production more sustainable. However, intensive egg production challenges hen health, inducing severe osteoporosis and the incidence of bone fractures. In this study, the relationship between bone quality and egg production, and/or eggshell quality, was evaluated at the end of an extended laying cycle of 100 weeks, comparing groups of hens with different production and eggshell quality pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 33 publications
3
35
1
Order By: Relevance
“…Medullary bone was clearly more mineralised in both breeds when housed in pens. In this study, there is little apparent correlation between medullary bone and bone strength, but other studies have found association between medullary mineralisation and bone strength (Alfonso-Carrillo et al, 2021; Rodriguez-Navarro et al, 2018). Thus, variation in medullary bone is an important contributor to variability in bone mineral content and mechanical properties, both in terms of genetic variation and response to exercise.…”
Section: Discussioncontrasting
confidence: 80%
“…Medullary bone was clearly more mineralised in both breeds when housed in pens. In this study, there is little apparent correlation between medullary bone and bone strength, but other studies have found association between medullary mineralisation and bone strength (Alfonso-Carrillo et al, 2021; Rodriguez-Navarro et al, 2018). Thus, variation in medullary bone is an important contributor to variability in bone mineral content and mechanical properties, both in terms of genetic variation and response to exercise.…”
Section: Discussioncontrasting
confidence: 80%
“…As the egg cycle extended, the numbers of soft-shelled and cracked eggs increased, which may be attributed to reduction of Ca absorption, stress, or poor physical quality [52][53][54]. The current results indicate that hens fed Bacillus subtilis had a lower incidence of both soft-shelled and cracked eggs but there was no strong evidence of the improvement of eggshell strength and thickness [55].…”
Section: Discussionmentioning
confidence: 54%
“…Previous study reported that probiotic efficiency as a growth promotor is affected by multiple factors, such as the type of probiotics, the length of feeding time and concentration [31], the isolation sources of probiotics, breed of laying hens, and their life-stage [59]. In addition, Alfonso-Carrillo et al [54] indicated that the promotion of egg production, eggshell quality, and bone traits in laying hens can occur independently through dietary treatment. Therefore, we speculate that Bacillus subtilis is more likely to improve bone traits rather than egg or eggshell quality.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kim et al (2005) , high eggshell quality is associated with poorer bone quality, because hens that show high eggshell Ca deposition also show high bone Ca mobilization, increasing the incidence of fractures. Moreover, Eusemann et al (2018) showed that the bone fracture incidence was reduced in a low-producing line compared to a high-producing line Conversely, Alfonso-Carrillo et al (2021) did not show any correlation between eggshell quality (eggshell percentage, eggshell thickness, and eggshell breaking strength) and bone quality during an extended laying cycle of 100 wk. According to these authors, bone characteristics and eggshell characteristics are independent and could be improved separately.…”
Section: Discussionmentioning
confidence: 85%